Molecular approaches for eco-epidemiological studies of Paracoccidioides brasiliensis - Richini-Pereira, Virgínia Bodelão [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Theodoro, Raquel Cordeiro [UNESP]; Macoris, Severino Assis da Graça [UNESP]; Bagagli, Eduardo [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2009)
Medical mycology has greatly benefited from the introduction of molecular techniques. New knowledge on molecular genetics has provided both theoretical and practical frameworks, permitting important advances in our understanding of several aspects of pathogenic fungi. Considering Paracoccidioides brasiliensis in particular, important eco-epidemiological aspects, such as environmental distribution and new hosts were clarified through molecular approaches. These methodologies also contributed to a better understanding about the genetic variability of this pathogen; thus, P. brasiliensis is now assumed to represent a species complex. The present review focuses on some recent findings about the current taxonomic status of P. brasiliensis, its phylogenetic and speciation processes, as well as on some practical applications for the molecular detection of this pathogen in environmental and clinical materials.
Keywords: Paracoccidioides brasiliensis; eco-epidemiology; PCR